Sectioned calorimeter for quick diagnostic of the electron beam energy distribution - Egorov I. S. Ivan Sergeevich; Serebrennikov M. A. Maksim Anatoljevich; Isakova Yu. I. Yulia Ivanovna; Poloskov A. V. Artem Viktorovich (2017, 2017)
Title screen